2017
DOI: 10.54386/jam.v19i4.603
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of maize (Zea mays L.) productivity and yield gap analysis using simulation modelling in subtropical climate of central India

Abstract: Quantifying the yield potential of maize at any given site is a key to understand the existing yield gaps and to identify the most important constraints in achieving optimal yield and profit. A well parameterized and validated APSIM model was used to assess the productivity and yield gap of maize cv Kanchan 101 from multi-year long-term and completed experiments. A total of 30 districts with 74 soil profiles of Madhya Pradesh were considered for the study. For the 30 selected sites, the rainfed potential yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The MAE (10.3), MBE (10.3) and RMSE (11.03) (Table 2) analysis also supported that the model slightly overestimated all the cases value. Mohanty et al, (2017) also found the model to overestimate days to physiological maturity stage in maize. The lower maximum temperature during tasseling to dough stage and higher solar radiation at silk emergence to physiological maturity could be favorable parameters for better grain yields under second date of sowing (Singh et al, 2013).…”
mentioning
confidence: 86%
“…The MAE (10.3), MBE (10.3) and RMSE (11.03) (Table 2) analysis also supported that the model slightly overestimated all the cases value. Mohanty et al, (2017) also found the model to overestimate days to physiological maturity stage in maize. The lower maximum temperature during tasseling to dough stage and higher solar radiation at silk emergence to physiological maturity could be favorable parameters for better grain yields under second date of sowing (Singh et al, 2013).…”
mentioning
confidence: 86%
“…As the most important animal fodder crop with the largest global production among cereals in the world, maize certainly has been attracting scholarly attention for improving its potential yield. A well parameterized and validated Agricultural Production Systems IMulator (APSIM) model was used for assessing the productivity and yield gap of maize in Madhya Pradesh of India [18], the Food and Agriculture Organization (FAO) AquaCrop model was evaluated for its predictability potential of maize growth and yields in Uganda [19], and the AquaCrop and AgroC models were calibrated and validated by using the data sets from 2015 (cool/dry season) and 2016 (warm/wet) respectively to investigate maize development and suitability in cool climate in Lithuanian of USA [20]. The AquaCrop model was evaluated relatively to maize growth, yield, and water use parameters/variables under different water stress conditions over six years (2005)(2006)(2007)(2008)(2009)(2010) in Nebraska of USA [21], while the Environmental Policy Integrated Climate (EPIC) model was assessed for its potential to simulate maize yield using limited data from field trials on maize in the eastern Cape of South Africa [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on estimating potential yield of maize through modelling have provided a number of important insights as follows. Agricultural Production Systems IMulator (APSIM) model was parameterized and validated to assess the productivity and yield gap of maize in Madhya Pradesh of India (Mohanty et al, 2017), while the APSIM crop model was applied for investigating the interaction between sowing date and cultivar in Khuzestan province of southwestern Iran (Rahimi-Moghaddam et al, 2018). An integrated crop simulation model-satellite imagery method was used for determining the maize yield gap in four major watersheds in Golestan Province of Iran (Pourhadian et al, 2019), while the DSSAT and data assimilation scheme (DSSAT-DA) was used for estimating maize yield and evaluating the sensitivity of maize yield to hydro-climatic variables (Liu et al, 2019), and three crop simulation models (AEZ-FAO, DSSAT-CERES-Maize and APSIM-Maize) were calibrated and evaluated to estimate maize potential and attainable yields in Brazil and to assess the performance of different ensemble strategies to reduce their uncertainties for maize yield prediction (Duarte and Sentelhas, 2019).…”
mentioning
confidence: 99%